Comparison studies of GSH isolation from several Malaysian local fruits by mechanical methods - Baiti, Arif Afraha; Jamal, Parveen; Mirghani, Mohamed Elwathig Saeed (2010)
Glutathione (GSH) is a simple tripeptide produced by the liver. It is a volatile substance, which is sweet in taste, comprised of the amino acids cysteine, glutamic acid and glycine. In these modern days, the use of traditional medicine by the suffers of chronic disease is encouraged due to the adverse effects of chemical drugs and treatment using medicines of natural origin appears to offer more gentle means of managing such disease. Therefore, the practice of traditionally used natural plants as medicines is one of the alternative ways to cure the illnesses. Besides, this study was done in order to investigate the production of GSH from fruits since most of the studies that had been conducted before were done on the isolation of GSH from other sources. In this study the reduced glutathione (GSH) was isolated from a potential local fruit of Malaysia. Three mechanical methods; homogenizer, ultrasonic and autolysis were screened for disrupting the fruits cells for maximum GSH content. Different methods of cell disruption gave different effect on the GSH production. Watermelon (Citrullus lanatus) is the best potential local fruit that contain higher GSH followed by Jackfruit (Artocarpus heterophylus) and Sapodilla (Manilkara zapota), while ultrasonic is the best cell disruption method which can give the maximum amount of GSH, followed by homogenizer method and autolysis method.